Towards High Performance Chemical Vapour Deposition V2O5 Cathodes for Batteries Employing Aqueous Media - Vernardou,D; Drosos,C; Kafizas,A; Pemble,ME; Koudoumas,E (Molecules, 2020)
The need for clean and efficient energy storage has become the center of attention due to the eminent global energy crisis and growing ecological concerns. A key component in this effort is the ultra-high performance battery, which will play a major role in the energy industry. To meet the demands in portable electronic devices, electric vehicles, and large-scale energy storage systems, it is necessary to prepare advanced batteries with high safety, fast charge ratios, and discharge capabilities at a low cost. Cathode materials play a significant role in determining the performance of batteries. Among the possible electrode materials is vanadium pentoxide, which will be discussed in this review, due to its low cost and high theoretical capacity. Additionally, aqueous electrolytes, which are environmentally safe, provide an alternative approach compared to organic media for safe, cost-effective, and scalable energy storage. In this review, we will reveal the industrial potential of competitive methods to grow cathodes with excellent stability and enhanced electrochemical performance in aqueous media and lay the foundation for the large-scale production of electrode materials.